2019
DOI: 10.1017/s000711451900103x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between usual food intake and faecal sterols and bile acids: results from the Cooperative Health Research in the Augsburg Region (KORA FF4) study

Abstract: Animal sterols, plant sterols and bile acids in stool samples have been suggested as biomarkers of dietary intake. It is still unknown whether they also reflect long-term habitual dietary intake and can be used in aetiological research. In a subgroup of the Cooperative Health Research in the Augsburg Region (KORA FF4) study, habitual dietary intake was estimated based on repeated 24-h food list and a FFQ. Stool samples were collected according to a standard operating procedure and those meeting the quality cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Moreover, our derived dietary pattern included fried potatoes, which were enriched with fat after processing, and their intake was correlated with higher bile acid concentration across the pattern. Yet, due to their fat content, the identification of processed meat, margarine, and fried potatoes as major food groups in this pattern was in line with a recent population based study, which observed a positive correlation between intakes of meat, processed meat, potatoes, and vegetables oils and fecal bile acid concentrations [54].…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, our derived dietary pattern included fried potatoes, which were enriched with fat after processing, and their intake was correlated with higher bile acid concentration across the pattern. Yet, due to their fat content, the identification of processed meat, margarine, and fried potatoes as major food groups in this pattern was in line with a recent population based study, which observed a positive correlation between intakes of meat, processed meat, potatoes, and vegetables oils and fecal bile acid concentrations [54].…”
Section: Discussionsupporting
confidence: 88%
“…Our study also did not control for other possible variables that could have affected our results, including dietary intake and definitively excluding other malabsorption conditions. Studies have shown that a high-fibre and low-fat diet results in lower faecal bile acid concentrations 21 , 22 . However, as patients undergoing SeHCAT scans are not advised to undergo any dietary restrictions before or during the testing time, we wanted to maintain the same guidance for consistency.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have focused on plasma lipid metabolites between such associations so far. Some studies examined the metabonomics characteristics of plasma or feces in a wide range of food groups, including eggs, but had not shown much interest in lipid metabolites ( Guertin et al, 2014 ; Mitry et al, 2019 ). Other studies combined eggs with other foods, such as ham, as a feed intervention to investigate consumers' metabolomics characteristics, but the results can not reflect the metabolite changes caused by egg consumption alone ( Rådjursöga et al, 2019 ; Rådjursöga et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%